Book review: Jan Breman, The Poverty Regime in Village India: Half a Century of Work and Life at the Bottom of the Rural Economy in South Gujarat. (May 2023) - Vrishali,
Jan Breman, The Poverty Regime in Village India: Half a Century of Work and Life at the Bottom of the Rural Economy in South Gujarat . Oxford University Press, 2007, 544 pp., ₹795. ISBN: 9780195690835.